“At 100 percent” assessment - Rudak, Leszek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2015)
The article presents the proposal for rules for granting a pass out of mathematics for business studies. The proposed schema guarantees that each student demonstrates a mastery of all the required skills, not only 60 or 70 percent as at the traditional exams. The proposed organization also eliminates the need for time-consuming repeated checking solutions of similar tasks written by the same student. The idea of the assessment procedure is based on two rules: (1) students must demonstrate that they have mastered all the required knowledge and all the skills, having three attempts; (2) each subsequent attempt includes only the previously failed topics. The proposed system was introduced on a trial basis at the Faculty of Management at the University of Warsaw, where it was subject to the assessment of circa 150 students. The conclusions and examples of students’ comments have been provided in the article.
Didactics of Mathematics, 2015, Nr 12 (16), s. 111-116
Keywords: teaching of quantitative subjects; assessment system; evaluation of students’ progress